A rare consortium of functional neurological disorder and Fahr’s disease - a herald of extensive calcification - Chauhan, Alka; Garg, Sunny (Asian Journal of Medical Sciences, 2020)
Fahr’s disease is also known as familial idiopathic basal ganglia calcification affecting the cerebral microvessels and presenting with numerous neuropsychiatric manifestations. Functional neurological disorder (FND), a pure neuropsychiatric phenomenon occurs rarely in Fahr’s disease. Herein, we have presented a case of 17 year old female presenting neuropsychiatric symptoms like pseudoseizure, left sensorineural deficit and mild headache for last 4 months. Mental status examination revealed impaired attention and concentration. Laboratory examinations were within normal limits except CT scan and MRI Brain which revealed bilateral and symmetrical basal ganglia calcification. This is a rare case of FND associated with Fahr’s Disease, never reported in the literature. This case highlights the need for evaluating the biological factors in causation of FND where psychological factors were not assessed.